Studies on antitussive effect of Tectona grandis roots using a cough model induced by sulfur dioxide gas in guinea pigs - Atul Kaushik; Meena Kumari; Anghesom Ambesajir (International Journal of Phytomedicine, 2011)
Objectives: Anti-tussive drugs are among the most widely used medications world wide; however no new class of drugs has been introduced into the market by keeping this point in mind. This attempt is made by testing a root of a well known timber tree Tectona grandis. Materials and methods: Here in, we have analyzed the polar compounds of Tectona grandis roots using chemical and biological methods. In this study, in vivo antitussive activity of root extracts (methanol and water) of Tectona grandis Linn. f. (Verbenaceae) was evaluated using a cough model induced by sulfur dioxide gas in rats. Results and Discussion: Treatment with aqueous extract and methanol extract at 500 mg/kg p.o. dose level showed more anti-tussive effect as compared with the dose level of 250mg/kg p.o. Differences between means were assessed by one way analysis of variance (ANOVA),followed by Dunnett’s test using sigma stat software. Both the extracts (methanol and water) significantly (P<0.05) suppressed the asthmas at the dose level of 500mg/kg.Phytochemical tests showed that methanol and water extracts tested positive for carbohydrates, reducing sugars, alkaloids, glycosides, flavonoids, sterols and saponins. Conclusion: This study provides a scientific basis on ethno medical uses of this plant. Further exploration in drug development of antitussives from Tectona grandis can focus on the purity activity relationships (PAR studies).